Troponin I and Major Adverse Cardiovascular Events in Acute Coronary Syndrome : Are They Related? - Jessi Vania Tambarta; Aryfa Andra , Cut; Rohmawati, Lili; Atiyatul Amra, Aryani (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background : Coronary Artery Disease (CAD) is one of the leading cause of death globally. The most threatening manifestation of CAD is Acute Coronary Syndrome (ACS), that classified as Unstable Angina Pectoris (UAP), Non ST Elevation Myocardial Infarction (NSTEMI) and ST Elevation Myocardial Infarction (STEMI). ACS patients tend to have complication, that usually defined as Major Adverse Cardiovascular Events (MACE) which  consists of heart failure, arrhythmia, stroke, and in-hospital mortality. Some factors have been researched to predict MACE in ACS, such as troponin level, which has been one of the modality to diagnose ACS. This study aims to determine the association between cTnI level and MACE in ACS patients at Adam Malik General Hospital. Method : This study used an observational analytic method with cross sectional design and retrospective approach. The data used is a secondary data that meets the inclusion and exclusion criteria. Result : Among 190 patients, 170 patients (89,5%) were >45 years old and 114 patients (75,8%) were male. The most common type of ACS was NSTEMI, with 73 patients (38,4%). cTnI level was increased in 131 patients (68,9%). There were 115 patients (60,5%) who experienced MACE and were dominated by heart failure, with 78 patients (41,1%). There was an association found between troponin level and MACE  (p=0,000). Conclusion : There was an association  between troponin level and MACE in ACS patients.